Reflexões sobre a luta na periferia do capitalismo: Frente de Luta Popular - Renata Mena Brasil do Couto (Argumentum, 2020)
The new phase of capitalism, triggered by the economic crisis of the 1970’s, caused a profound shaking-up of the world’s critical thinking, making us rethink existing forms of political action. We will discuss the impacts of this rethinking on Brazilian social movements and the emergence of a new type of social protagonism, whose identity and actions grow from the inability of individuals to participate in the relationship between capital and labour and in universal competition as the common and general form of societal life. Based on extensive documentary research, we will analyse the trajectory of the Frente de Luta Popular (The Front for Popular Struggle), a social movement that reinvented the strategies and scenarios of struggle, transforming the City into a priority area for social disputes and conflicts, with the occupation of public buildings in Rio de Janeiro at the centre of their actions.